Yaguará, tierra soberana: propuesta arquitectónica para un complejo turístico y eco hotel (Huila) (2020)
The research aimed to design a tourist complex connecting us as a final destination to a beautiful ecohotel; managing to involve the population of the same municipality, empowering it in the economic, cultural and environmental aspects, highlighting the attractiveness of the area that it offers to tourists, since the project is located in a strategic part that even the same tourist admires, being in the neighboring part of the Magdalena river reservoir. The project had a development of a methodological procedure in which the phases and stages of the research and design process of the tourist complex and the ecohotel were structured, for which an analysis of the municipality in which the offer and the demand through a diagnosis. The results of this diagnosis showed that it is possible to build a tourist complex that also has an accommodation service in the municipality of Yaguara in the department of Huila. The investigation concluded that the implementation of said complex will allow the development of the municipality in the cultural, environmental and tourist part, achieving the economic improvement of the sector by increasing the influx of local and foreign visitors.